Blood Lipid Profile and Yolk Cholesterol Content of Coturnic coturnix japonica Receiving African Leaf (Vernonia amygdalina) Extract in Drinking Water - Dwi Margi Suci; Kurnia Laila Fadilah; Lilis Khotijah (Jurnal Ilmu Peternakan Terapan, 2023)
The aim of this study was to determine the effect of supplementation of African leaf (Vernonia amygdalina) extract on quail blood lipid profile (comprising total cholesterol, triglyceride, HDL cholesterol, LDL cholesterol concentrations) and yolk cholesterol. One hundred twenty female quail aged 8 weeks were fed a supplementary Vernonia amygdalina for 6 weeks. The study was of completely randomized design with 3 treatment and 5 replications. The treatment were no supplementation of African leaf extract to the control and supplementation of African leaf extract at doses of 3 and 6 ml quail/day. The observed variables were those of blood lipid profile (comprising total cholesterol, triglycerides, HDL cholesterol, and LDL cholesterol concentrations) and egg yolk cholesterol. Blood lipid profiles data were analyzed of variance and yolk cholesterol concentrations were analyzed descriptively with 1 sample (composite from each replication) for each treatment. The study results showed that African leaf extract significantly (P<0.05) reduced quail blood cholesterol and yolk cholesterol. Yolk cholesterol was reduced by 5.01% and 11.38, respectively, at doses of 3 and 6 ml quail/ day as compared to controls. Blood triglyceride, HDL cholesterol, and LDL cholesterol concentrations were not significantly different from those in controls. From these study results it was concluded that supplementation of African leaf at a dose of 6 mL quail/ day was capable of reducing quail blood cholesterol and yolk cholesterol.